A Water Pump Efficiency With Automatic Sensors To Increase Operational Efficiency - Akbar, Al Athur; Massaguni, Massriyady (JEAT : Journal of Electrical Automation Technology, 2024)
This review discusses the performance and efficiency of water pumps equipped with automatic sensors to increase operational efficiency in various industrial and household sectors. Water pumps play an important role in water distribution systems, but the main challenges that often arise are high energy consumption and performance problems. This research explores the integration of automated sensors that can monitor and regulate pump performance in real time, enabling adjustments according to dynamic operational conditions. By using sensors to measure important parameters such as pressure, flow and temperature, this system can increase energy efficiency and prevent pump damage in the first place. Research findings show that use of this technology can provide significant energy savings, extend pump life, and improve overall system efficiency. This research provides practical solutions for industry in optimizing water pumping systems more efficiently and environmentally friendly.